2022
DOI: 10.3390/biomedicines10092254
|View full text |Cite
|
Sign up to set email alerts
|

The Pathological Mechanisms of Hearing Loss Caused by KCNQ1 and KCNQ4 Variants

Abstract: Deafness-associated genes KCNQ1 (also associated with heart diseases) and KCNQ4 (only associated with hearing loss) encode the homotetrameric voltage-gated potassium ion channels Kv7.1 and Kv7.4, respectively. To date, over 700 KCNQ1 and over 70 KCNQ4 variants have been identified in patients. The vast majority of these variants are inherited dominantly, and their pathogenicity is often explained by dominant-negative inhibition or haploinsufficiency. Our recent study unexpectedly identified cell-death-inducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 124 publications
(94 reference statements)
1
6
0
Order By: Relevance
“…40,41 The last group of genes that showed nominally significant relationship with speech and or language phenotypes were known to be contributory to hearing loss: GJB2 and KCNQ1 . 42,43 The breadth of the genetic diagnoses spectrum illustrates the various dimensions of potential aetiologies of speech impairment, ranging from epileptic encephalopathies to movement disorders and hearing loss, mirroring the findings of our phenotypic-based analysis. Disentangling speech and language phenotype-genotype association warrants further examination; we identified several relationships, but no genes that would be explanatory for speech and language impairments alone were identified in our cohort.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…40,41 The last group of genes that showed nominally significant relationship with speech and or language phenotypes were known to be contributory to hearing loss: GJB2 and KCNQ1 . 42,43 The breadth of the genetic diagnoses spectrum illustrates the various dimensions of potential aetiologies of speech impairment, ranging from epileptic encephalopathies to movement disorders and hearing loss, mirroring the findings of our phenotypic-based analysis. Disentangling speech and language phenotype-genotype association warrants further examination; we identified several relationships, but no genes that would be explanatory for speech and language impairments alone were identified in our cohort.…”
Section: Discussionsupporting
confidence: 53%
“…40,41 The last group of genes that showed nominally significant relationship with speech and or language phenotypes were known to be contributory to hearing loss: GJB2 and KCNQ1. 42,43 The breadth of the genetic diagnoses spectrum illustrates the various dimensions of potential aetiologies of speech impairment, ranging from epileptic encephalopathies to movement disorders and hearing loss, mirroring the findings of our phenotypic-based analysis.…”
Section: Discussionmentioning
confidence: 57%
“… 29 , 30 The genetic mutations of KCNQ1 gene have been reported to be related to type 2 diabetes, 31 cardiovascular diseases 32 and deafness. 33 , 34 Thus far, only a GWAS research of Han Chinese found a correlation of KCNQ1 variants with gout while not hyperuricemia, 14 which mechanisms supposed be responsible of immune regulation. The amplification of inflammation of KCNQ1 blocker intervention in our gout mouse model was consistent with the hypothesis that KCNQ1 mediates gouty inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…This study KCNQ4 was explored the expression and prognosis of in human malignant tumors. Many studies have shown that KCNQ4 is a member of voltage-gated potassium channel, and the decrease of KCNQ4 activity caused by gene mutation is the cause of non-syndromic hearing loss [32] . In the nervous system, the KCNQ4 subunit is present in a subpopulation of cholinergic neurons in the peduncular pontine nucleus, suggesting that it contributes to the regulation of the sleep-wake cycle [33] .…”
Section: Page 9/27mentioning
confidence: 99%